Pulmonary Complications in Children Following Hematopoietic Cell Transplantation: A Case Report and Review of the Diagnostic Approach - Elbahlawan, Lama; McArthur, Jenny; Morin, Cara E.; Abdelhafeez, Hafeez; McCarville, M. Beth; Ruiz, Robert E.; Srinivasan, Saumini; Qudeimat, Amr (Frontiers in Oncology, 2021)
Pulmonary complications are common in children following hematopoietic cell transplantation (HCT) and contribute to their morbidity and mortality. Early diagnosis is essential for management and prevention of progression of lung injury and damage. In many cases, diagnosis can be challenging and may require diagnostic imaging and more invasive testing such as bronchoscopy and lung biopsy. We report the case of a 12-year-old girl who developed recurrent episodes of acute respiratory failure requiring intensive care unit admission in the post-HCT phase and describe the diagnostic and multidisciplinary approach for her management. In addition, we review the diagnostic approach of pulmonary complications post-HCT and highlight the utility and risks of bronchoscopy and lung biopsy in these children.